Complex ballot propositions, individual voting behavior, and status quo bias - Zohal Hessami; Sven Resnjanskij (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper analyzes how the complexity of ballot propositions influences individual voting behavior in direct-democratic elections. We combine micro-data from representative post-referendum surveys in Switzerland with unique data on a novel measure of proposition complexity which relies on a word count of information provided in official booklets. Using Heckman estimations to correct for participation bias, we provide evidence that proposition complexity leads to rejection-biased voting (status quo bias). An increase of one standard deviation in our complexity measure is associated with an average increase in the rejection rate by 5.3 percentage points. However, correcting for the participation bias reduces the effect by 2.3 percentage points highlighting the importance of selection effects in determining vote outcomes. Further evidence suggests cognitive overburdening as the transmission channel and excludes alternative explanations.
Keywords: D71; D72; D81; 330